Evaluation of the Likelihood of Establishing False Codling Moth (Thaumatotibia leucotreta) in Australia via the International Cut Flower Market - Xingyu Li; Robert N. Emery; Grey T. Coupland; Yonglin Ren; Simon J. McKirdy (Insects, 2022)
Kenya and some other African countries are threatened by a serious pest Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae), the false codling moth. The detection of T. leucotreta is quite difficult due to the cryptic nature of the larvae during transportation and is therefore a concern for Australia. This insect is a known pest of agriculturally important crops. Here, Maxent was used to assess the biosecurity threat of T. leucotreta to Australia. Habitat suitability and risk assessment of T. leucotreta in Australia were identified based on threatened areas under suitable climatic conditions and the presence of hosts in a given habitat. Modeling indicated that Australia is vulnerable to invasion and establishment by T. leucotreta in some states and territories, particularly areas of western and southern Australia. Within these locations, the risk is associated with specific cropping areas. As such, invasion and establishment by T. leucotreta may have serious implications for Australia’s agricultural and horticultural industries e.g., the fruit and vegetable industries. This study will be used to inform the government and industry of the threat posed by T. leucotreta imported via the cut flower industry. Targeted preventative measures and trade policy could be introduced to protect Australia from invasion by this pest.